PENGARUH UMPAN BALIK PEKERJAAN RUMAH TERHADAP RASA TANGGUNG JAWAB DAN HASIL BELAJAR MATEMATIKA - yarso, Noviani; Zubaidah, Zubaidah; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to find out the difference in students who had given homework feedback when compared with the students had not homework feedback to responsibility and learning outcomes in mathematics on the students of flat build class seven grades in SMP Negeri 10 Pontianak. The method in this research used experimental and quasy experimental design. Sample of the research were consisted of 30 students of seven B grades as experiment and 30 students of seven C class as a control. The result showed that the average sense responsibility and mathematics learning outcomes of students who had given homework feedback was higher than students had not given its. The results of analysis the data, it obtained there were the differences in students who had given homework feedback than students had no homework feedback to learning outcomes and responsibility of students seven grades in SMP Negeri 10 Pontianak. It showed the average responsibility was equal to 57,17 in the control and class experiment 59,83 for the average learning outcomes in control class by 65 and in the experimental class 72.Keywords: Homework Feedback, Responsibility, Learning Outcomes Â